Application of a c‐Si Solar Cell with a Three‐Dimensional Structure to Indoor Photovoltaics. Issue 7 (20th January 2022) - Sim, Yeon Hyang; Yun, Min Ju; Lee, Dong Yoon; Cha, Seung I.
Abstract: As individual photovoltaic (PV) power sources for indoor conditions, various types of solar cells including organic, perovskite, and dye‐sensitized devices, have been used because they provide better performance under weak lighting conditions; however, they are limited in terms of durability and applicability to larger‐sized cells and modules. Crystalline silicon (c‐Si) solar cells address these issues as an economical alternative. Here, to overcome low performance under weak lighting conditions, such as indoor lighting, a three‐dimensional structured c‐Si solar cell is developed to enhance the surface area of the cell for improved indirect light acquisition. With our design prototype, the power output increases by nearly two‐fold using a tetrahedron‐structured c‐Si solar cell compared to its flat two‐dimensional counterpart. Further improvements in the power output are expected to be achieved for the 3‐D c‐Si solar cell by minimizing mismatch losses, which is a common problem associated with this PV device. Abstract : For indoor photovoltaics, usage of diffused light should be considered to increase electric power output. In order to omnidirectional light capturing, three‐dimensional cell arrays are used for indoor‐energy harvesting photovoltaics. The three‐dimensional crystalline silicon solar cell units show two‐fold power output with high diffused light condition under a light‐emitting diode light source with enlarged surface area.